Hanguana rubinea Škorničk. & P.C.Boyce (Hanguanaceae), a new record for Indonesia - Irsyam, Arifin; Galingging, Ades; Wijaya, Kesuma; Dewi, Asih; Peniwidiyanti; Anshori, Zakaria; Hariri, Muhammad; Rosleine, Dian; LeoNG-Škornickova, Jana (BRIN Publishing (Penerbit BRIN), 2025)
IRSYAM, A. S. D., GALINGGING, A., WIJAYA, K., DEWI, A. P., PENIWIDIYANTI, AL ANSHORI, Z., HARIRI, M. R., ROSLEINE, D. & LEONG-ŠKORNIČKOVÁ, J. 2025. Hanguana rubinea Škorničk. & P.C.Boyce (Hanguanaceae), a new record for Indonesia. Reinwardtia 24(1): 33‒39. — Hanguana rubinea Škorničk. & P.C.Boyce, originally described from and reported to be endemic to Singapore, has been discovered on Batam, Riau Islands, Sumatra and is reported here as a new record for Indonesia. The distinguishing features of H. rubinea include the silky indumentum on the abaxial surface of its leaves, the striking ruby-red hue of fruits, and the unique bowl-shaped seeds. Description and colour plates prepared from the ripe fruiting material in Batam are included together with additional notes and a map reflecting the current distribution of this species